2011
DOI: 10.1007/s10646-011-0809-8
|View full text |Cite
|
Sign up to set email alerts
|

Reference genes for qPCR assays in toxic metal and salinity stress in two flatworm model organisms

Abstract: The flatworm species Schmidtea mediterranea and Macrostomum lignano have become new and innovative model organisms in stem cell, regeneration and tissue homeostasis research. Because of their unique stem cell system, (lab) technical advantages and their phylogenetic position within the Metazoa, they are also ideal candidate model organisms for toxicity assays. As stress and biomarker screenings are often performed at the transcriptional level, the aim of this study was to establish a set of reference genes for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
4
21
0
Order By: Relevance
“…Primer efficiencies were calculated as E = 10 -1/slope on a standard curve, and efficiencies of 0.85 to 1.15 were tolerated. Reference genes were selected according to geNorm analysis (adjusted from Plusquin et al, 2012). Gene expression data were calculated relative to the reference gene following the 2 -ΔΔ Ct method (Livak and Schmittgen, 2001).…”
Section: Gene Expressionmentioning
confidence: 99%
“…Primer efficiencies were calculated as E = 10 -1/slope on a standard curve, and efficiencies of 0.85 to 1.15 were tolerated. Reference genes were selected according to geNorm analysis (adjusted from Plusquin et al, 2012). Gene expression data were calculated relative to the reference gene following the 2 -ΔΔ Ct method (Livak and Schmittgen, 2001).…”
Section: Gene Expressionmentioning
confidence: 99%
“…This was also true in a study of Plusquin et al . in which reference genes for flatworms were validated (Plusquin et al ., ). Thus it is strongly advised that validation of reference genes should be done for every new experimental setup.…”
Section: Discussionmentioning
confidence: 97%
“…The non‐stability of commonly used reference genes has also been proven in many other cell types, including those in plants (Remans et al ., ; Wang et al ., ), bacteria (Jacob et al ., ), flatworms (Plusquin et al ., ), insects (de Boer et al ., ), fish (Small et al ., ) and mammals (Nelissen et al ., ) under different experimental conditions. In contrast, there are also studies, which found that many of the widely used housekeeping genes or reference genes are stable in a given experimental setup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primer efficiencies were calculated as E = 10 −1/slope – 1 on a standard curve generated using a fourfold dilution series of one sample over at least five dilution points that were measured in triplicate, and efficiencies of 0.85–1.15 were tolerated. Reference genes were chosen as described in Material and Methods part 2 of Plusquin et al, . Gene expression data were calculated relative to the reference gene following the 2 ‐ΔΔCt method (Livak and Schmittgen, ).…”
Section: Methodsmentioning
confidence: 99%